Sensate Vision: From Maximum Visibility to Haptic Erotics - Janssen, Sara (feminists@law, 2016)
For years, moving-image pornography has been shaped by a desire for “maximum visibility,” according to film scholar Linda Williams (1999), informing pornography’s formulaic and repetitive graphic depiction of the mechanics of the sexual act, as well as its intense scrutiny of the female body, and its different generic tropes, the most important one being the so-called “money shot,” consisting of the external male ejaculation. However, in the course of the last two decades, a corpus of feminist, lesbian, and queer pornography has appeared, which not only expresses a particular interest in bringing to screen female sexual pleasure, but also problematizes pornography’s obsession with maximum visibility, instead seeking to convey the tactile and visceral “feel” of the sexual encounter. By taking up Laura Marks’s concept of “haptic visuality” as a particular feminist strategy, this article takes into account two examples of alternative pornography, namely Touch (2013) and One Night Stand (2006), in order to describe the ways in which these films not only appropriate the carnal appeal of pornography, but also reconfigure it, experimenting with different ways of visualizing female sexuality, and opening up not only what pornography might look like, but also what it might do.